AKIBAT HUKUM DARI TINDAKAN CYBERSQUATTING DI INDONESIA (ANALISIS PUTUSAN PENGADILAN DALAM PERKARA PENDAFTARAN NAMA DOMAIN EBAY.CO.ID) - Bathara, Manik; Puspita Shara, Made Cinthya (Kertha Desa; Vol 10 No 7 (2022), 2022)
The purpose of this study was to provide an understanding to the public regarding the legal regulation of domain name registration in Indonesia and to examine the legal consequences of cybersquatting actions carried out based on the Central Jakarta District Court Decision Number 299/PDT.G/2013/PN.JKT.PST in the case of using the ebay.co.id domain name. This normative legal research examines the problem of norms in the form of vague norms based on an approach to legislation and the analysis process of court decisions. Based on the results of research conducted related to the legal regulation of domain name registration in Indonesia, it is based on the provisions contained in the ITE Law and Permenkominfo No. 23 of 2013 concerning Domain Name Management by adhering to the principle of “first come first serve”. Then with regard to the legal consequences that arise from the act of cybersquatting in Indonesia, it is examined based on a court decision in the ebay.o.id domain name case, including the inclusion of the action as an unlawful act where an understanding of the principle of "first come first serve" registration cannot be justified if it is linked in the presence of bad faith to benefit from the existence of well-known trademark rights owned by other parties.